Arctic Sessions of the St. Petersburg International Economic Forum (SPIEF-2024) - Valery P. Zhuravel (Арктика и Север)
The article summarizes the general results of the 27th St. Petersburg International Economic Forum (SPIEF-2024, Forum), which took place in St. Petersburg from 5 to 8 June 2024. The author participated in two main Arctic sessions, which were devoted to the Northern Sea Route and international aspects of Arctic development, and interacted with practitioners from federal and regional ministries and transport companies. This article is devoted to analysing these sessions.